Characteristics and management of sinonasal paragangliomas: a systematic review. Issue 4 (20th December 2018) - Nguyen, Brandon K.; Patel, Nirali M.; Arianpour, Khashayar; Svider, Peter F.; Folbe, Adam J.; Hsueh, Wayne D.; Eloy, Jean Anderson
Abstract : Background: Paragangliomas of the nasal cavity and paranasal sinuses, although exceedingly rare, can exhibit frequent and aggressive recurrences. Our objective was to evaluate tumor characteristics, clinical course, management, and associated complications of sinonasal paragangliomas Methods: A systematic review of the literature was performed utilizing the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) guidelines, searching for sinonasal paraganglioma. Studies meeting inclusion criteria were assessed for level of evidence. Patient demographics, tumor characteristics, primary intervention, and other clinical characteristics were evaluated. Results: Forty‐five relevant studies encompassing 54 patients with sinonasal paraganglioma were identified. The most common tumor locations were the nasal cavity (66.7%), ethmoid sinuses (22.2%), maxillary sinuses (7.4%), and sphenoid sinuses (3.7%). Common presenting symptoms included recurrent epistaxis (68.5%), nasal obstruction (53.7%), and headache (13.0%). Tumors were malignant in 28.6% of patients. Only 4 cases (7.4%) involved functional tumors. Initial management was always surgical, via either an open (63.0%) or endoscopic (33.3%) approach. Radiotherapy was used as adjunctive treatment in 10 cases (18.5%). Recurrence rate was 21.7% and occurred between 12 to 156 months after initial resection. The overall survival was 87.0% with a metastatic rate of 8.7%. Conclusion: Sinonasal paragangliomas are vascular neoplasms manifesting clinically with recurrent epistaxis and nasal obstruction. Management goals are total resection with clear margins and long‐term follow‐up due to tendency for local recurrence. Radiotherapy has been utilized as adjuvant therapy with variable results. Further randomized controlled studies may be invaluable in elucidating these findings.